Study of Carbon Nanotubes with a Casson Fluid in a Vertical Channel of Porous Media under MHD and Dufour Effect - Hazarika, S.; Ahmed, S. (Journal of Scientific Research, 2021)
An analysis is conducted to investigate the problem of heat/mass transfer in MHD free convective flow of Casson-fluid in a vertical channel embedded with saturated porous medium past through carbon nanotubes in the form of single-wall carbon nanotubes (SWCNTs) and multiple-wall carbon nanotubes (MWCNTs) with engine oil as base fluid. In this article, the impact of CNT’s on velocity, temperature, shear stress and rate of heat transfer of the nanofluid has been investigated and studied graphically for the effects of different key physical parameters involved. The validity of this flow model is presented and is found satisfactory agreement with published results. The results state that, fluid velocity accelerates for greater values of Casson parameter and nanoparticles volume fraction, while thermal radiation (R) and heat generation (Q) assume a significant role in CNT's. Applications of this study arise in broad area of science and engineering such as thermal conductivity, energy storage, biomedical applications, air and water filtration, fibers and fabrics.